Antimicrobial activity of Desmos chinensis leaf and Maclura cochinchinensis wood extracts - Sopa Kummee; Niwan Intaraksa (Songklanakarin Journal of Science and Technology (SJST), 2008)
The antimicrobial activity of crude extracts of Desmos chinensis leaves and Maclura cochinchinensis wood were tested against human pathogens, including bacteria, yeast and dermatophytic fungi, using the agar disc diffusion and agar dilution methods. The crude chloroform extract of D. chinensis was active against Staphylococcus aureus, Staphylococcus epidermidis and Bacillus subtilis with MIC values ranging from 500-1000 μg/ml. The crude hexane and chloroform extracts of D. chinensis exhibited the strongest activity against all dermatophytes tested (Trichophyton rubrum, Trichophyton mentagrophytesand Microsporum gypseum), with MIC values ranging from 31.25-62.50 μg/ml. However, methanol and water extracts of D. chinensis showed no activities against all of the microorganisms tested. The crude chloroform extract of M. cochinchinensis exhibited strong antibacterial activity against S. aureus, S.epidermidis and B. subtilis with MIC value ranging from 125-250 μg/ml. and showed inhibition against all the dermatophytes, with MIC of 250 μg/ml. Hexane extract of M. cochinchinensis was not active against all microorganisms. None of the crude extracts were active against Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Shigella sonnei and Candida albicans. These findings indicated that D. chinensis and M. cochinchinensis had antibacterial activity against Gram-positive bacteia and anti-dermatophytic activity.